Piscicidal Effects of Terminalia arjuna Leaf, Bark and Fruit Extract on a Fresh Water Predatory Catfish, Heteropneustes fossilis - Akter, Suely; Zabed, Hossain M.; Nasiruddin, Munira; Qi, Xianghui (Research in Ecology, 2020)
Piscicidal effects of several solvent extarcts (distilled water, 50% ethanol, absolute ethanol and 80% methanol) of Terminalia arjuna leaves, barks and fruits were studied against a common fresh water predatory fish, Heteropneustes fossilis under laboratory conditions in terms of Behavior and mortality of fishes after 24 h. Fishes exposed to plant extracts showed agitating movement with quick surfacing, loss of balance, mucus secretion, and finally died. The LC50 values of distilled water, 50% ethanol, absolute ethanol and 80% methanol extracts were found to be 311.726, 236.141, 183.541, 478.794 ppm for leaves, 117.894, 96.998, 38.990, 304.193 ppm for barks and 1400.033, 949.209, 555.201, 875.158 ppm for fruits, respectively. Chi-square values were found to be insignificant at P<0.05 in almost all plant extracts, indicating that observed and expected mortalities did not vary significantly in relation to doses, except 80% methanol extract of barks and absolute ethanol extract of fruits. The F-values of treatments were significant at P<0.01, except 80% methanol extract of fruits, in which F-values were insignificant in all replicates at P>0.01. Based on LC50 values, order of piscicidal activity followed the pattern, bark > leaf > fruit extracts. Order of piscicidal activity for the extracts was like absolute ethanol > 50% ethanol > distilled water > 80% methanol for leaf and bark, while for fruit extracts, trend was like absolute ethanol > 80% methanol > 50% ethanol > distilled water.